Roles, detection, and visualization of neutrophil extracellular traps in acute pancreatitis - Li, Hongxuan; Zhao, Lingyu; Wang, Yueying; Zhang, Meng-Chun; Qiao, Cong (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) are produced in large quantities at the site of inflammation, and they locally capture and eliminate various pathogens. Thus, NETs quickly control the infection of pathogens in the body and play vital roles in immunity and antibacterial effects. However, evidence is accumulating that NETs formation can exacerbate pancreatic tissue damage during acute pancreatitis (AP). In this review, we describe the research progress on NETs in AP and discuss the possibility of NETs as potential therapeutic targets. In addition, since the current detection and visualization methods of NETs formation are not uniform and the selection of markers is still controversial, a synopsis of these issues is provided in this review.